Symposium 2: Engaging First Year Chemical Engineering Students With Video-Based Course Material - Campbell, Grant M.; Garforth, Arthur A.; Bishop, Andrew (Proceedings of the International Conference on Networked Learning, 2004)
This paper describes a project in which lectures and other supplementary material were captured on video and presented in a CD-based package suitable for students studying first year chemical engineering. Video clips, animated PowerPoint™ presentations and text-based material were combined using Microsoft Producer™, with the various components accessible through a web-style interface, and the package delivered to student on CD’s. The package was evaluated using the “Three I’s” framework of Young and Asensio (2002): Image, Interactivity and Integration. Interactivity was key to the pedagogical effectiveness of the package and the enthusiastic response from the students. The package, by combining text, video, slides and quizzes, successfully integrated several elements of communication; future work will also aim to integrate taught material across subject boundaries. The issue of Engagement – ensuring that the students actually engage with the material in a way that delivers a meaningful educational experience – was also identified as a key requirement (Kearsley and Shneiderman, 1999; Hodgson and Asensio, 2001). In the first part of the project, selected 50 minute classroom lectures on Heat Transfer were captured on video and made available to students subsequent to the lecture, not as a replacement to the live lecture, but intended as supplementary to the lecture as a basis for revision. This initiative was envisaged to have three benefits: (i) the style of lecturing adopted for the initial creation of the video gave variety, which maintained interest; (ii) the mode of learning was altered, both in the lecture and subsequently under the student’s own initiative and control, giving greater opportunity to capture and engage students who perhaps did not respond so well to traditional classroom lecturing; and (iii) the opportunity to revisit spoken explanations of subtle concepts was valuable during revision. A slight downside during the initial creation of the videos was that students were unable to ask questions during the lecture, as they would normally do. As a contrasting approach, in the second part of the project shorter video clips related to 1st Year Chemical Reaction Engineering were created. These clips were typically 10 minutes in length and prepared “off-line” (i.e. not in the live classroom environment). These were intended to provide review of key course components and to aid the students to recognise the advantage of course revision. The different “off-line” style was adopted to give variety and again help engage the student. Tutorial questions were provided that appeared automatically following the end of each clip. The project was evaluated through student feedback questionnaires, which showed overwhelming enthusiasm for the initiative. Particularly attractive was the control given to the students to receive lecture material at their own pace and under their own control, and the variety and interest the material added to the course. Practical issues included guarding against any temptation on the part of students to miss the live lectures and, related to this, the most appropriate timing for dissemination of the CD’s, as well as the practicalities of creating the video material and the delivery package. Video clips of laboratory practicals was identified as potentially beneficial and appealing, and future work will aim to add these to the suite of material available. This project was funded through an ExxonMobil Higher Education Support Scheme award and facilitated through the Click and Go Video project (http://www.clickandgovideo.ac.uk ).